Representation of the Old Age in the Towns of the Polish-Lithuanian Commonwealth in the Late Medieval and Early Modern Times - Гошко, T. (Київський національний університет імені Тараса Шевченка, 2018)
From ancient times, philosophical treatises divided human life into separate periods. The most extreme of them were childhood and old age. If the first of these stages is relatively well represented both in legal literature and documentary sources, the second one is paid much less attention. There was no clear dating of the beginning of old age. The attitude towards older people was ambivalent, which was dictated by both Christian views and the practice of life. These views were widespread in the towns of the Polish Lithuanian Commonwealth in the 16th and 17th centuries. The town law to some extent protected older people, but in most cases, they did not act as subjects of law. The important groups of sources for the history of old age are the codes of law and burghers' testaments.

У філософських трактатах від найдавніших часів людське життя поділялося на окремі періоди. Крайніми з них були дитинство і старість. Якщо перший із цих етапів відносно добре представлений як у правовій літературі, так і в актових джерелах, то другому приділяли значно менше уваги. Не було чіткого датування початку старості. Ставлення до людей старшого віку було амбівалентним, що диктувалося як християнськими поглядами, так і практикою життя. Ці уявлення були поширеними і в містах Речі Посполитої XVI–XVII ст. Міське право певною мірою захищало людей старшого віку, але в більшості випадків вони не були суб'єктами права. Важливими групами джерел до історії старості є кодекси права та міщанські заповіти.
Уявлення про старість у містах річпосполитського простору на межі Середньовіччя та ранньомодерної доби
Keywords: Middle Ages; early modern period; Polish-Lithuanian Commonwealth; stages of human life; old age; town; town law; Середньовіччя; ранньомодерна доба; Річ Посполита; періоди життя людини; старість; місто; міське право